PRAKTEK DISKRIMINASI KAPASITAS KARGO OLEH LION AIR GROUP (STUDI KASUS PUTUSAN KPPU NOMOR 07/KPPU-I/2020) - Estri Dewangga Cadipa Jati (2022)
Discriminatory practice is an activity that is prohibited in competition law because discriminatory practice do not provide equal opportunities to every business actor in the relevant market. One of them is the alleged discriminatory practice of cargo capacity by PT Lion Mentari, PT Batik Air, PT Wings Air and PT Lion Express or Lion Air Group in KPPU's Decision Number 07/KPPU-I/2020. There is a collaboration between PT Lion Mentari, PT Batik Air and PT Wings Air with PT Lion Express to provide a cargo capacity of 40 (forty) tons per day on flight routes from Hang Nadim Airport to Soekarno Hatta Airport, Halim Perdana Kusuma Airport, Juanda Airport and Kualanamu Airport, making it difficult for other agents to deliver their cargo. This study uses a normative legal research method with a statue approach and a case approach where the data source is obtained from secondary data collected by library research and to process the data carried out by qualitative analysis. After conducted the research with analysis of the relevant market, the fulfillment of the elements of article 19 letter d and the discriminatory practice itself, it is stated that PT Lion Mentari, PT Batik Air and PT Lion Express have violated Article 19 letter d of Act. No. 5 of 1999. Meanwhile, PT Wings Air was not found guilty because it did not own the route. The fines that do not need to be activated by PT Lion Mentari, PT Batik Air and PT Lion Express are due to the short period of discriminatory practices and no significant impact of the discriminatory practice